Psychiatric Morbidity and its Correlations in Diabetic Patients in a Tertiary Care Hospital - Jayasree, Kurupatha Menatha; Stephen, Sirisha; Haritha, Kottedi; Humerakhan, Pathan; Kumar, Ganesh (Indian Journal of Pharmacy Practice)
Background: Diabetes is a chronic, disease with life altering consequences, which effects virtually every organ in the human system. Co-existence of psychological symptoms and DM becomes a grave challenge for the clinicians as both illnesses worsen the outcomes. Depression/ Anxiety is one of the raising causes of seeking health care. Presence of psychiatric symptoms seriously impairs the health-related quality of life among diabetic patients. Psychiatric symptoms can decrease adherence to self-care practices, contributing to higher HbA1c levels. Individuals with diabetes are having 2 to 4 times greater risk of psychological distress when compared to individuals without diabetes. Materials and Methods: This prospective, observational study was conducted in the department of Psychiatry 150 patients were enrolled into the study who attended the outpatient department. Discussion: Among 150 subjects, majority of the study subjects 119 (79%) were found to be anxiety condition than depression at the time of assessment. The subjects with depression were found to be 28 (17%) The presence of depression among subjects who are taking Insulin, OHA, both were found to be 11.5%, 4.6% and 1% respectively. The distribution of anxiety in subjects who are taking Insulin, OHA, both were found to be 8%, 51.3% and 19.3% respectively. Conclusion: The study found a high proportion of anxiety among patients with T2DM.Therefore the care of individuals with DM should include the screening and possible treatment of anxiety in order to achieve and sustain treatment goals.
Keywords: Diabetes mellitus; Depression; Anxiety; Insulin; Oral hypoglycaemics; Psychiatric illness; Stress; HbA1c; Fasting blood glucose level; Post prandial blood glucose level